The role of prebiotics in dairy calf performance, health, and immune function - Payne, Caleigh (Kansas State University, 2015)
Rapid responses in milk production to changes in dairy cow management, nutrition, and health give producers feedback to help optimize the production and health of dairy cattle. On the contrary, a producer waits up to two years before the investments in calf growth and health are observed thru lactation. Even so, performance, health, and immune status during this time play a large role in subsequent cow production and performance. A recent report from the USDA’s National Animal Health Monitoring System estimated that 7.6 to 8.0% of dairy heifers die prior to weaning and 1.7 to 1.9% die post-weaning (2010). The cost of feed, housing, and management with no return in milk production make for substantial replacement-heifer cost. Therefore, management strategies to improve calf health, performance, and immune function are needed. Prebiotic supplementation has gained interest in recent years as a method to improve gastrointestinal health and immune function in livestock. It has been provided that prebiotic supplementation may be most effective in times of stress or increased pathogen exposure throughout the calf’s lifetime (McGuirk, 2010; Heinrichs et al., 2009; Morrison et al., 2010). Multiple studies have researched the effect of prebiotics around the time of weaning, but to the author’s knowledge, none have focused on prebiotic’s effects during the transition from individual housing prior to weaning to commingled housing post-weaning which may also be a time of stress or increased pathogen exposure. Therefore, a study was conducted to determine the effects of prebiotic supplementation of mannan-oligosaccharide and beta-glucan during this commingling phase. The results indicate that prebiotic supplementation alters feeding behavior, modulates neutrophil function, and increases antibody response during this time. The purpose of industry-based research, such as studies on prebiotics and other methods to improve calf health and performance, is to provide producers with tools to advance and improve their operations. In this respect, it is beneficial to learn what producers’ needs are and what they are interested in improving. An extension survey was conducted to establish priorities, need, and management practices of Kansas dairy producers. The results of the survey indicate that nearly half of the producers (49.3%) are interested in extension programs focused on calf/heifer management. Similarly, over half (54.8%) of the producers responded that they are interested in improving calf/heifer management in the next 5 years. The death loss observed as well as the results of the survey display a need and a producer desire to improve calf management, warranting research on prebiotics and further methods to continue to improve calf health and performance
Keywords: Dairy; Calves; Prebiotics; Animal Sciences (0475)